2013
DOI: 10.1111/eth.12196
|View full text |Cite
|
Sign up to set email alerts
|

Darwin's Finch Begging Intensity Does Not Honestly Signal Need in Parasitised Nests

Abstract: Parental care should be selected to respond to honest cues that increase offspring survival. When offspring are parasitised, the parental food compensation hypothesis predicts that parents can provision extra food to compensate for energy loss due to parasitism. Chick begging behaviour is a possible mechanism to solicit increased feeding from attending parents. We experimentally manipulated parasite intensity from Philornis downsi in nests of Darwin's small ground finch (Geospiza fuliginosa) to test its effect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
63
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 54 publications
(66 citation statements)
references
References 41 publications
3
63
0
Order By: Relevance
“…Medium tree finch nests had more P. downsi larvae compared with most other Darwin's finch species (Dudaniec et al, 2007;Kleindorfer et al, 2014b). Although higher body condition is often linked with fewer parasites or higher survival under conditions of parasitism (Brown et al, 2000;Møller et al, 1998), this does not directly apply here because the parasite P. downsi consumes the blood of nestling birds and not adults Fessl et al, 2006;Huber, 2008;O'Connor et al, 2014). Therefore, even if adult small and medium tree finches had better body condition and higher adult survival than the hybrid birds, their numbers could still be declining due to low nesting success.…”
Section: Discussionmentioning
confidence: 97%
“…Medium tree finch nests had more P. downsi larvae compared with most other Darwin's finch species (Dudaniec et al, 2007;Kleindorfer et al, 2014b). Although higher body condition is often linked with fewer parasites or higher survival under conditions of parasitism (Brown et al, 2000;Møller et al, 1998), this does not directly apply here because the parasite P. downsi consumes the blood of nestling birds and not adults Fessl et al, 2006;Huber, 2008;O'Connor et al, 2014). Therefore, even if adult small and medium tree finches had better body condition and higher adult survival than the hybrid birds, their numbers could still be declining due to low nesting success.…”
Section: Discussionmentioning
confidence: 97%
“…Adult flies, which are not parasitic, lay their eggs in the nests of finches and other land birds in the Galápagos. In some years, 100% of finch nests fail to produce fledglings due to P. downsi (Koop et al 2011, 2013a, O'Connor et al 2013. Several studies have shown that P. downsi reduces the reproductive success of the medium ground finch (Geospiza fortis) and other species of Darwin's finches (reviewed in Koop et al 2011).…”
mentioning
confidence: 99%
“…() showed that provisioning in 2010 did not differ between treatments, as found in other Darwin's finch systems (O'Connor et al. ).…”
Section: Discussionmentioning
confidence: 68%
“…, , O'Connor et al. ), is harmless to birds, including newly hatched nestlings. Nests were sprayed soon after the first nestling hatched, then again 4–6 d later.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation